The brave little tailor - Grimm, Jacob, 1785-1863; Grimm, Wilhelm, 1786-1859; Bell, Anthea; Svend Otto S. (Svend Otto Sørensen), 1916- (Larousse, 1979)
Through cleverness a young tailor who kills seven flies with one blow becomes a King.